Using online journals to improve the teaching of reflection among preservice math teachers. Issue 3 (4th May 2022) - De Leon-Pineda, Josephine Luz; Prudente, Maricar
ABSTRACT: Teacher education institutions need to provide reflection opportunities for preservice teachers to develop their reflection level. This study investigated the impact of online reflection journals on the reflection level of preservice math teachers (PMTs) and their experiences. A mixed-method action research was utilised in the study. The twenty-four PMTs in a state university in the Philippines were the participants in the study. A rubric was used to evaluate their reflection level, while semi-structured interview and their reflection outputs were used to triangulate the results. Quantitative results revealed a significant increase in the reflection level of the PMTs, while the qualitative findings support the results. Hence, this study suggests the use of an online reflection journal to provide a venue for PMTs to reflect on their learning experiences in their mathematics courses.